Nursing department students’ knowledge and use of complementary and alternative medicine methods - Pirinçci, Edibe; Kaya, Ferit; Cengizhan, Sultan; Onal, Fulya (My University, 2018)
Aim: This study was conducted to evaluate the knowledge, use and views of health school nursing students about complementary and alternative medicine (CAM) practices.Materials and Methods: In this descriptive study, the questionnaire was distributed to every student who was studying on the days when the research was applied. The study was conducted with 489 volunteer students who agreed to fill out the questionnaire. The obtained data were recorded in SPSS packaged software and statistical analyzes were done through this software.Results: The CAM methods that are most known by the students who participated in the research are respectively, (82.6%) exercise, (79.6%) vitamins, (74.0%) diet, (73.0%) vegetable products and (71.3%) massage. The frequency of using CAM was found to be 51.3%. CAM usage rate in males is higher than females (p<0.05). In this study, when the causes of using CAM were examined, 51.1% of the students stated that they used CAM methods to solve their health problems, 50.1% of them used CAM to reduce stress and 44.4% of them used CAM for hair and facial treatment. The rate of recommending CAM methods to others is 52.6%. The students were informed about CAM methods firstly from the internet, secondly from the family and thirdly from the friends.Conclusions: Students of the nursing department have a lack of knowledge in this regard. Nevertheless, more than half of the students have used alternative treatment methods and recommended them to others.
Keywords: Tamamlayıcı ve Entegre Tıp; Sağlık Bilimleri ve Hizmetleri; Hemşirelik